Thermodynamics and dielectric properties of KH₂PO₄, RbH₂PO₄, KH₂AsO₄, RbH₂AsO₄ ferroelectrics - Levitskii, R.R.; Lisnii, B.M.; Baran, O.R. (Condensed Matter Physics, 2001)
Within the proton ordering model with taking into account the short-range
and long-range interactions as well as tunnelling effects, in the framework
of the cluster approximation, we study the thermodynamic and static dielectric
properties of the KH₂PO₄ type ferroelectrics. Theoretical results are
compared with the corresponding experimental data and with the results
of theoretical calculations of other sources. We show that under the proper
choice of the theory parameters, a very good quantitative description
of the available experimental data is obtained for the temperature dependence
of spontaneous polarization, specific heat, longitudinal and transverse
static dielectric permittivities, as well for the Curie-Weiss temperature
and constant.
Suitability of the model for the description of experimental data for the crystals
KH₂PO₄, RbH₂PO₄, KH₂AsO₄, RbH₂AsO₄ without taking into account
striction, fluctuations, and other effects is discussed. В рамках моделі протонного впорядкування з врахуванням короткосяжних і далекосяжних взаємодій та тунелювання протонів на водневих зв’язках досліджуються в наближенні чотиричастинкового кластера термодинамічні та статичні діелектричні властивості сегнето-електриків типу KH₂PO₄. Проведено кількісне порівняння результатів
теоретичного розрахунку з відповідними експериментальними даними та з результатами розрахунків інших авторів. Показано, що при
належному виборі параметрів теорії має місце дуже добрий кількісний опис наявних експериментальних даних для температурних залежностей спонтанної поляризації, теплоємності, поздовжньої і поперечної статичних діелектричних проникностей, а також для температури та константи Кюрі-Вейса.
Обговорюється придатність моделі до опису кристалів KH₂PO₄,
RbH₂PO₄, KH₂AsO₄, RbH₂AsO₄ без врахування стрикції, флуктуацій та
інших ефектів.